Neuropsychological examination of patients with epilepsy suffering from cognitive impairment - Blazhina, Ірина; Korostiy, Володимир (Psychosomatic Medicine and General Practice, 2019)
Background. Deviation of cognitive functions is the most common pathology among psychiatric and neurological diseases. Qualitative diagnostics of these deviations at the dodementical stage will improve the cognitive field, which respectively will lead to the preservation of the social functioning of patients. The nosological conditionality of this pathology is quite diverse. Thus, cognitive impairment is caused by neurodegenerative diseases, vascular brain pathology, mixed vascular degenerative diseases, dysmetabolic encephalopathies, neuroinfectious and demyelinating diseases, cranial traumas, tumors, and other tumors. The main cognitive functions include perception, attention, memory, praxis, language, leadership, and social intelligence. Purpose. The study of the current state of the problem of the cognitive impairment, generalization of approaches of using pathopsychological research methods. Materials and methods. Various research methods are used to investigate cognitive impairment: observation, clinical interviewing, performance analysis, and the use of pathopsychological techniques. It was carried out the review and theoretical analysis of primary sources and modern scientific approaches of using diagnostic pathopsychological techniques for the purpose of examining cognitive functions. Results. This publication presents a review of scientific literature of the current state of the problem of cognitive impairment. The principles of the pathopsychological examination of cognitive functions are highlighted. A brief review of the most common tests, scales and pathopsychological methods for the study of cognitive processes is presented, as well as possible causes of false cognitive research results. Conclusion. Nowadays researchers distinguish different degrees and clinical variants of cognitive impairment. Modern neurocognitive tests are aimed not only to identify symptoms of cognitive decrease and to assess its degree, but also to the study of certain cognitive functional clusters («dementia» and «submention»). This approach allows for targeted correction by training relevant cognitive functions using simulators and computer programs. Important is a comprehensive study of the mental state of a patient with epilepsy, taking into account the effect of depressive symptoms on the functioning of the cognitive sphere.